صورة الجزائر العلمية في المتن الرحلي المغاربي -ابن زاكور الفاسي انتخابا - صليحة, قروي (جامعة الوادي - University of Eloued, 2021)
يلعب أدب الرحلة دورا كبيرا في تجلية خصوصيات الثقافة المنظورة، وبخاصة إذا كانت الرحلة علمية، وهذا ما بينه النص الرحلي للأديب ابن زاكور الفاسي الذي قَدِم إلى الجزائر سنة 1683م، للتعلّم على علمائها وطلب إجازاتهم العلمية. تحاول هذه الدراسة رصد صورة الجزائر العلمية من خلال عدسات هذا الرحالة المغربي، لتقف على حدود تفاعلها الثقافي في محيطها المغاربي، ومساعيها في توسيع آفاق معرفة أبنائه. وقد خلص البحث إلى أن متنه الرحلي الشاهد على حدود التثاقف والتجسير يعدّ مرجعا مهما يجلي الوجه المشرق لتاريخ الجزائر الثقافي والعلمي، ومدى إشعاعيته على كل المنطقة في تلك الفترة. Travel literature plays a major role in showing visible culture specificities, especially when the journey is a scientific expedition. In this respect, travel writings of Ibn Zakour Al-Fassi, a Moroccan traveler who came to Algeria in 1683 acquiring knowledge from its erudites and scholars, have provided valuable information about the cultural and scientific climate in Algeria back then. This study aims at investigating the scientific image of Algeria through this traveler eyes to determine its cultural interactions limits within the Maghrebian context, and its credit for expanding knowledge all over the region. The research concluded that Ibn Zakour’s travel writings, that witness acculturation and intellectual bridging, serve as important references in unveiling the bright side of Algerian cultural and scientific history, and its intellectual enlightenment extent over the whole region in that age.
مقال
Keywords: الأدب الرحلي ابن زاك ; ر الفاسي التثاقف ; التجسير الإشعاع الفكري الإجازات العلمية.